Emissions of 2, 3, 7, 8-substituted and non-2, 3, 7, 8-substituted polychlorinated dibenzo-p-dioxins and dibenzofurans from secondary aluminum smelters. (January 2019) - Li, Haifeng; Liu, Wenbin; Tang, Chen; Lei, Rongrong; Wu, Xiaolin; Gao, Lirong; Su, Guijin
Abstract: The secondary aluminum smelting industry is an important source of polychlorinated dibenzo- p -dioxin and dibenzofurans (PCDD/Fs). However, the formations and emissions of non-2, 3, 7, 8-PCDD/Fs have rarely been studied. Non-2, 3, 7, 8-PCDD/Fs may also be metabolically toxic to mammalians. In this study, four typical secondary aluminum smelters were selected as demonstration smelters and the composition of the raw material they used was adjusted to investigate the influence on PCDD/F emissions and profiles. In addition to 17 congeners of 2, 3, 7, 8-PCDD/Fs, 64 congeners of non-2, 3, 7, 8-PCDD/Fs were firstly reported. Strong, positive correlations were found between non-2, 3, 7, 8-PCDD/Fs and 2, 3, 7, 8-PCDD/Fs. The concentrations of 2, 3, 7, 8-PCDD/Fs in stack gas and fly ash samples were 120.7–870.4 pg/Nm 3 and 13.40–292.9 ng/g, respectively. Those of non-2, 3, 7, 8-PCDD/Fs in the stack gas and fly ash samples were 84.03–1183.7 pg/Nm 3 and 7.20–344.7 ng/g, respectively. The raw material composition was a key factor affecting PCDD/F emissions and profiles. An analysis of Gibbs free energies (Δ G f ) showed that non-2, 3, 7, 8-PCDD/Fs could be transformed into 2, 3, 7, 8-PCDD/Fs, which would increase the PCDD/F environmental risks. The emission inventories of 2, 3, 7, 8-PCDD/Fs, non-2, 3, 7, 8-PCDD/Fs, and International Toxic Equivalents from Chinese secondary aluminum smelters in 2013 were 8247 g, 7253 g, and 608.6 g, respectively. The results of this study could contribute to potential risk evaluations and effective reduction of non-2, 3, 7, 8-PCDD/Fs. Graphical abstract: Highlights: Emission of 2, 3, 7, 8-PCDD/Fs and non-2, 3, 7, 8-PCDD/Fs was investigated. The impacts of raw material composition on PCDD/F levels and profiles were studied. Non-2, 3, 7, 8-PCDD/Fs can be transformed into 2, 3, 7, 8-PCDD/Fs, elevating risks. PCDD/F concentrations increased as the content of dirty aluminum scrap increased.